Sinergi Fungsi Sosial Dan Komersial BMT Al-Ittihad Rumbai Pekanbaru Sebagai Bentuk Dakwah Ekonomi - Kamila Rakhmawati; Azwar; Nanda Putri (https://journal.metanusantara.com/jenius/index.php/jem, 2026)
This research aims to examine the synergy between the social and commercial functions of Baitul Maal wat Tamwil (BMT) Al-Ittihad Rumbai Pekanbaru as a real manifestation of Islamic economic preaching. The background of this research is based on the phenomenon that BMT as a sharia microfinance institution not only plays a role in business activities, but also carries a social mission through the management of zakat, infak, alms, and waqf (ZISWAF) funds, but in its implementation the two functions have not fully run in a balanced and synergistic manner. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews and direct observations at the headquarters of BMT Al-Ittihad Rumbai, Pekanbaru. The research results show that the commercial function of BMT Al-Ittihad runs through the collection of funds based on the wadiah and mudharabah contracts, as well as the distribution of financing with the murabahah, musyarakah, and mudharabah contracts. As for its social function, it is realized through the management of ZISWAF funds, the provision of scholarships, and the financing of Qardhul Hasan's virtues. The synergy of the two is proven to create an inclusive economic chain, where the benefits from the commercial sector support the sustainability of social programs, while the empowerment of the dhuafa community through social functions transforms into productive partners for the commercial sector.